Georissus substriatus Heer, 1841 (Coleoptera: Georissidae) in the Iberian Peninsula; rectification the records from Portugal - Shatrovskiy, A. G. (The Kharkiv Entomological Society Gazette, 2026)
Georissus substriatus is recorded for the first time for Spain, according to revised data, for Portugal is given new locality, according to re-identification of the specimen from the collection of Manuel Paolino de Oliveira (University of Coimbra). An overview of the general distribution of the species is given and a map is provided. 4 figs, 14 refs.